STRATEGI PROMOSI JOGJA T-SHIRT OMAH OBLONG DALAM MEMBANGUN BRAND AWARENSS (Studi Kasus di Jogja T-Shirt Omah Oblong, Jl. Wachid Hasyim 7c, Ngaben Yogyakarta) - Atika Noprida (2011)

(untitled)
Jogja T-shirt Omah Oblong, Jogja Cultural T-Shirt Center is one of company that budge in merchandise and shirt cultural selling in Yogyakarta. Was born at 2009, 17th August. At the first time the company held a spectacular event, made a "big shirt" with size 36 meter x 44 meter the biggest jogja cultural pictorial in Indonesia. Appropriate by selling data that got from counting of book selling every four months, that describe by selling point frequently. the selling level was increase at the fir